Risk Analysis of Depression, Sleep Hygiene Level and Chronic Disease with Insomnia in Elderly - Nilam P.I Warni Sayekti; Lucia Y. Hendrati (Jurnal Berkala Epidemiologi, 2015)
Elderly is the final stage of life so often experience various changes and disorders, one of which is a sleep disorder or insomnia. The prevalence of insomnia in the elderly is quite high, which is more than 60%, but the appearance of this disorder is often ignored. This study aims to identify and analyze the risk of depression, sleep hygiene, and the presence of chronic diseases in the elderly with insomnia cases. This research was conducted analytically observational with a case-control research design. The research location is Jombang Elderly Social Service and is carried out on 40 elderly people. The study population was divided into 2, namely 20 case populations and 20 control populations. The variables studied were depression, chronic illness, sleep hygiene, and the incidence of insomnia. Most elderly suffer from early insomnia with symptoms of severe difficulty initiating sleep. early morning awakening is the least symptoms experienced by the elderly. Depression (OR = 22,667), chronic illness (OR = 6,926) and sleep hygiene (OR = 11,000) showed a significant relationship with the incidence of insomnia. The conclusion in this study is perpetuating (chronic disease) and precipitating (sleep hygiene) factors play a role in the emergence of insomnia in the elderly, so it is advisable to take action to control chronic diseases and pay more attention to sleep disorders experienced by the elderly, and the need for actions to improve and improve sleep hygiene.